2012
DOI: 10.1002/pssb.201248051
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between the electron work function and yield strength of metals

Abstract: In this study, an effort is made to establish the correlation between electron work function (EWF) and mechanical properties of metals such as yielding strength and hardness. In general, the intrinsic resistance of metals to plastic deformation depends on their atomic bond strength that is essentially governed by the electron behavior. Based on the Peierls–Nabarro model, an intrinsic sixth‐power dependence of the yield strength of metals on their EWF is derived. Such a relation can also be extended to hardness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 15 publications
2
42
0
Order By: Relevance
“…It has been demonstrated that the mechanical behaviors (including bulk modulus, Young's modulus, hardness, and yield stress) of metals can be characterized by their electron distributions. 34,54,59,[62][63][64] As shown in, our predicted EWF of Mg agrees well with previous experimental 52 and theoretical data. 65 By selecting different reference states, the variations of EWF (Du 1 and Du 2 ) are defined as:…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…It has been demonstrated that the mechanical behaviors (including bulk modulus, Young's modulus, hardness, and yield stress) of metals can be characterized by their electron distributions. 34,54,59,[62][63][64] As shown in, our predicted EWF of Mg agrees well with previous experimental 52 and theoretical data. 65 By selecting different reference states, the variations of EWF (Du 1 and Du 2 ) are defined as:…”
Section: Resultssupporting
confidence: 91%
“…As mentioned previously, many efforts have been made to correlate the concentration of solute atoms to the variation of hardness in Mg alloys, 24,34,35 and the hardness of metal materials has been correlated with EWFs. 54,64 In the next section, the EWF and hardness of Mg-Gd-based alloys will be discussed. EWF and Hardness of Mg-Gd/Y-Zn-Zr-Ag Alloys Figure 6 shows the effect of solute atoms on the age-hardening behavior and the EWF-dependent hardness of Mg-Gd-TM (TM = Ag, Zn, and Zr) alloys.…”
Section: Resultsmentioning
confidence: 99%
“…5(a) -schematic illustration). In this case, the material having a higher EWF should have a larger adhesive force, since the atomic bond energy is proportional to ϕ 6 [17][18][19] and a larger atomic bond energy results in a higher surface energy (for surfaces having the same broken-bond density) [1,15,20]. The EWFs of both stainless steel samples are higher than that of Ti1, thus their larger frictional coefficients are expected.…”
Section: Resultsmentioning
confidence: 99%
“…Valance electron concentrations and electron work functions To investigate the structure-property relationships in the exemplary HEAs and HE-MGs, we characterize interactions among the alloying elements using the electron work function, EWF, 18,[41][42][43] and the bonding charge density, Δρ.…”
Section: Configurations Of Heasmentioning
confidence: 99%
“…It can be used to predict the mechanical properties of metallic materials, such as Young's modulus, hardness, and yield strength. 42,43 In contrast, Δρ is known as the deformation electron density, characterizing chemical bonds via electron redistributions. Consequently, the subsequent response or redistribution of electrons under an applied normal/shear strain is directly measured by the change of Δρ, thus providing the necessary atomic and electronic bases for the deformation behavior of HEAs and HE-MGs, as it is discussed below.…”
Section: Configurations Of Heasmentioning
confidence: 99%